CRISPR/Cas9-Mediated Whole Genomic Wide Knockout Screening Identifies Specific Genes Associated With PM2.5-Induced Mineral Absorption in Liver Toxicity - Peng, Jinfu; Yi, Bin; Wang, Mengyao; Tan, Jieqiong; Huang, Zhijun (Frontiers in Bioengineering and Biotechnology, 2021)
PM2.5, also known as fine particles, refers to particulate matter with a dynamic diameter of ≦ 2.5 µm in air pollutants, that carries metals (Zn, Co, Cd) which can pass through the alveolar epithelium and enter the circulatory system and tissues. PM2.5 can cause serious health problems, such as non-alcoholic fatty liver and hepatocellular carcinoma, although the underlying mechanisms of its toxic effect are poorly understood. Here, we exposed L02 cells to PM2.5 and performed a pooled genome‐wide clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) to assess loss of function and identify new potential PM2.5targets. Enrichr and KEGG pathway analyses were performed to identify candidate genes associated with PM2.5 toxicity. Results revealed that four key genes, namely ATPase Na+/K+ transporting subunit alpha 2 (ATP1A2), metallothionein 1M (MT1M), solute carrier family 6 members 19 (SLC6A19) and transient receptor potential cation channel subfamily V member 6 ( TRPV6) were associated with PM2.5 toxicity, mainly in regulating the mineral absorption pathway. Downregulating these genes increased cell viability and attenuated apoptosis in cells exposed to PM2.5. Conversely, overexpressing TRPV6 exacerbated cell apoptosis caused by PM2.5, while a reactive oxygen species (ROS) inhibitor N-acetyl-l-cysteine (NAC) alleviated PM2.5-induced apoptosis. In conclusion, ATP1A2, MT1M, SLC6A19 and TRPV6 may be contributing to absorption of metals in PM2.5 thereby inducing apoptosis mediated by ROS. Therefore, they hold potential as therapeutic targets for PM2.5-related diseases.